Способ получения 2,4,6,8-тетраацетил-2,4,6,8-тетраазабицикло-[3.3.0]октан-3,7-диона - Яговкин А. Ю. Александр Юрьевич; Бакибаев А. А. Абдигали Абдиманапович; Филимонов В. Д. Виктор Дмитриевич
опубл. 20.12.95, Бюл. № 35